Impact of political and legal environments on international trade - Abugre, James Atambilla; Nellis, Joe; Ofosu-Dorte, David (Springer, 2024)
International trade has become increasingly important in the functioning of the global economy as a result of financial globalization and differences in resource endowments, prompting extensive economic research and increased demand for regional and global integration among nations and continents. International trade is one of the most salient changes in the world economy since 1980. However, many nations and other regional economic blocs have over the years instituted trade restrictions, tariffs, trade policies such as subsidies, and tax waivers among others to harness the potentials of economic comparative advantages in and within their jurisdictions. Political ideologies, instability, and insurgencies and risks are important factors that affect international trade across the globe. Legal regimes are equally important factors that determine the flow of free trade among nations. Civil and common law countries which have different focus of trade regulations and dividend policies are critical matters that affect trade decisions among MNCs and countries. This chapter examines the political and legal environments of international trade. In this chapter, we provide an overview of the emerging political and legal environments in Africa. We then discuss how the political as well as the legal environments and policy trends impact international trade of African countries.
Keywords: 38 Economics; 48 Law and Legal Studies; 3802 Econometrics; 16 Peace, Justice and Strong Institutions; Impact; International trade; political and legal environments